Patterns of Growth in Childhood in Relation to Adult Schooling Attainment and Intelligence Quotient in 6 Birth Cohorts in Low- and Middle-Income Countries: Evidence from the Consortium of Health-Oriented Research in Transitioning Societies (COHORTS). Issue 8 (12th May 2021) - Poveda, Natalia E; Hartwig, Fernando P; Victora, Cesar G; Adair, Linda S; Barros, Fernando C; Bhargava, Santosh K; Horta, Bernardo L; Lee, Nanette R; Martorell, Reynaldo; Mazariegos, Mónica; Menezes, Ana M B; Norris, Shane A; et al.
ABSTRACT: Background: Growth faltering has been associated with poor intellectual performance. The relative strengths of associations between growth in early and in later childhood remain underexplored. Objectives: We examined the association between growth in childhood and adult human capital in 5 low- and middle-income countries (LMICs). Methods: We analyzed data from 9503 participants in 6 prospective birth cohorts from 5 LMICs (Brazil, Guatemala, India, the Philippines, and South Africa). We used linear and quasi-Poisson regression models to assess the associations between measures of height and relative weight at 4 age intervals [birth, age ∼2 y, midchildhood (MC), adulthood] and 2 dimensions of adult human capital [schooling attainment and Intelligence Quotient (IQ)]. Results: Meta-analysis of site- and sex-specific estimates showed statistically significant associations between size at birth and height at ∼2 y and the 2 outcomes ( P  < 0.001). Weight and length at birth and linear growth from birth to ∼2 y of age (1 z -score difference) were positively associated with schooling attainment (β: 0.13; 95% CI: 0.08, 0.19, β: 0.17; 95% CI: 0.07, 0.32, and β: 0.25, 95% CI: 0.10, 0.40, respectively) and adult IQ (β: 0.74, 95% CI: 0.35, 1.14, β: 0.73, 95% CI: 0.35, 1.10, and β: 1.52, 95% CI: 0.96, 2.08, respectively). Linear growth from age 2 y to MC and from MC to adulthood was not associated with higher school attainment or IQ. Change in relative weight in early childhood, MC, and adulthood was not associated with either outcome. Conclusions: Linear growth in the first 1000 d is a predictor of schooling attainment and IQ in adulthood in LMICs. Linear growth in later periods was not associated with either of these outcomes. Changes in relative weight across the life course were not associated with schooling and IQ in adulthood.